THE FULFILLMENT OF THE RIGHT TO HEALTH FOR INDONESIAN CITIZENS ABROAD: A HUMAN RIGHTS AND ISLAMIC LAW PERSPECTIVE - Izadi, Fariz Farih; Setiawan, Dian Alan; Rohman, Abdul (JCH (Jurnal Cendekia Hukum), 2024)
This research aims to explore BPJS Kesehatan as a mechanism for fulfilling the right to health, Indonesia's responsibility in ensuring the fulfillment of the right to health, and to evaluate the realization of the right to health for citizens abroad in the context of human rights theory and Islamic law perspectives regarding health rights. This study employs a normative legal research method by examining various literature-based sources. The findings conclude that the social security system is implemented through a social insurance mechanism designed to ensure that all Indonesian citizens are protected under an insurance system, thereby enabling them to meet their basic health needs. The fulfillment of Indonesian citizens' health rights has been primarily focused on healthcare services. However, essential health prerequisites such as access to clean drinking water, adequate sanitation, sufficient nutrition, health-related information, environmental health, and workplace health still need to be fully met. Safeguarding life (hifzu nafs) is one of the maqasid al-shariah, where preserving life results from preventive and curative health efforts, allowing every citizen to maintain their well-being with a decent and mentally fulfilling life. It demonstrates that the state's fulfillment of the right to health is aligned with the concept of hifzu nafs, or the preservation of life.